The effect of regular running on body weight and fat tissue of individuals aged 18 to 65 - Kutac, Petr; Bunc, Václav; Buzga, Marek; Krajcigr, Miroslav; Sigmund, Martin (Journal of physiological anthropology, 2023)
BACKGROUND: Age and reduction in performed physical activity cause physiological changes that include an increase in body fat (BF) and visceral fat (VF) during aging. These parameters, together with increased body mass (BM), are some of the risk factors of several noninfectious diseases. However, changes in body composition can be influenced by regular physical activity. Running is a suitable, accessible, and the most effective physical activity cultivating people. The objective of this study is to investigate the effects of long-term, regular PA, specifically recreational running, on changes in body composition among recreational adult runners covering a weekly distance of at least 10 km, compared with inactive adult individuals within the same age bracket. METHODS: The study included 1296 runners and inactive individuals (691 male and 605 female), divided into 5 age groups: 18-25, 26-35, 36-45, 46-55, and 56-65 years. Runners are as follows: ran ≥ 10 km/week, and inactive is as follows: did not follow the WHO 2020 physical activity recommendations. The measured parameters included BM, BF, and VF. To check statistical significance, the Mann-Whitney U-test was used. Practical significance was assessed using the effect of size. RESULTS: All age groups of runners were selected to include individuals who run at least 10 km per week. In fact, they ran, on average, from 21.6 to 31.4 km per week in relation to age and showed significantly lower values of BM, BMI, BF, and VF (p < 0.05) than inactive individuals. Exceptions included insignificant differences (p > 0.05) in BM and BMI in males in the age category of 18-25 and in females in the age category of 18-25 and 26-35. CONCLUSION: The selected runners had to run at least 10 km per week. Their actual average volume was significantly higher (from 21.6 to 31.4 km/week), and the results showed that it could lead to significantly better body composition values. It may lead to significant changes in body mass, body fat, and visceral fat. It may meet the contemporary societal expectations for physical activities that are both achievable and effective at the lowest possible volume.
Keywords: cvičení; mladiství; Running; mužské pohlaví; Visceral fat; Body fat; Adult; Inactive individuals; Body Weight; složení těla; ženské pohlaví; Humans; tuková tkáň; tělesná hmotnost; Adipose Tissue; Exercise; Weight status; Body Composition; dospělí; běh; Female; Adolescent; lidé; Male